Characteristics of the post-thawed Balinese bull semen extended in three different extenders and equilibration times - Amal, A. S.; Arifiantini, R. I.; Setiadi, M. A.; Said, S. (Diponegoro University, 2019)
The objectives of the present study were to compare and determine the best post-thawed characteristics of balinese bull sperm cryopreserved in three different extenders; animal based (Tris-clarified egg yolk (Tris-cEY)), and non-animal based extenders (Bioxcell® (lecithin based) and Optixcell® (liposome based)) in combination with three different equilibration times (30 minutes, 2 hours, 4hours). Thirty six ejaculates were collected from six Balinese bulls and frozen in three extenders (Tris-cEY, Bioxcell® and Optixcell®) after equilibration in three different times (30 minutes, 2hours and 4hours). Computer-assisted sperm analysis (CASA), hypo-osmotic swelling test (HOST) and eosin nigrosin staining were used in the post-thawed semen analysis. There was a significant interaction between equilibration time and extender type for sperm motility, viability and membrane integrity. Thirty minutes equilibration time had the lowest values (P<0.05) for all the evaluated parameters independent of extender type. Overall, semen extended in Tris-cEY, Bioxcell® and Optixcell® were similarly better when equilibrated at 4 hours (P>0.05). Moreover, post-thawed semen which were extended in Optixcell® for 2 hours equilibration showed a better motility compared with the other extenders (P<0.05). In conclusion, two hours equilibration of semen with Optixcell® is sufficient for semen freezing. Four hours equilibration has the best sperm survival, independent of the extender type.